Outcome of laparoscopic nephrectomy in benign renal disease - Giri, Naresh Kumar; Thapa, Narayan; Thapa, Bikash Bikram; Bhandari, Bharat Bahadur; Hamal, Bhairab Kumar (Journal of Patan Academy of Health Sciences, 2016)
Introductions: Laparoscopic surgery is a rapidly emerging option in urology. With the advances in technology and instruments, currently this is viable alternative to treat complex surgical diseases as well as reconstructive surgery. Methods: This was a prospective observational study to analyze the outcome of laparoscopic nephrectomy. A total of 51 patients had undergone laparoscopic nephrectomy over the period of five years. The variables analyzed were, age, sex, operative time, estimated blood loss, length of hospital stay, conversion rate and complication. Results: The patients’ mean age was 41.1 years (range 15-71 years). Indications for nephrectomy were non-functional kidney secondary to stone disease in 26 (50.98%). Mean operative time was 1.43 hours. Median hospital stay was 2.3 days. Conclusions: Laparoscopic surgery is a safe and feasible treatment option for benign renal diseases with comparable outcomes. Non- functional kidney secondary to renal stone was the major cause of nephrectomy in this study. Journal of Patan Academy of Health Sciences. 2016 Dec;3(2):19-22